42. Japanese Society of Electronic Music (JSEM) Concert: A Tribute Celebrating Iannis Xenakis’s Centennial - Mikako Mizuno (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
On December 9, 2022, the JSEM (Japanese Society of Electronic Music) held a concert celebrating Xenakis’s centennial in Shibuya Densyo Hall, Japan. The year 2022 was also monumental year for JSEM as it represented the Society’s 30th anniversary. This concert featured a lecture by Takehito Shimazu, the diffusion of the eight prize-winning pieces of UPISketch International Competition, and the world premieres of five new pieces composed by JSEM composers and dedicated to Xenakis: 1. Kyohei Hayashi: Galactic Blood (fixed audio-visual) 2. Masahiro Oda: Vertigo (fixed audio-visual) 3. Osamu Kadowaki: mesure space X (fixed audio) 4. Satoshi Fukushima: uncountable structures I (fixed audio) 5. Mikako Mizuno: Rosehip Surface (fixed audio)